Impact of a Quality Improvement Intervention to Increase Brief Alcohol and Drug Interventions on a Level I Trauma Service. Issue 5 (May 2016) - Thomas, Princess; Seale, J. Paul; Johnson, J. Aaron; Dhabliwala, Jason; Kitchens, Debra; Okosun, Ike S.; Stokes, Nathan A.; Ashley, Dennis
Screening and brief intervention (SBI) decreases alcohol use and related consequences among trauma patients. Although SBI is required in Level I and II trauma centers, implementation often is difficult. This study used the Plan-Do-Study-Act approach to identify and implement measures to increase the number of patients receiving SBI at a Level I trauma center. A multidisciplinary Quality Improvement Committee with representation from the Trauma Service and SBI Team met monthly during 2011. Stepwise interventions included identifying a resident "champion" responsible for screening, brief intervention, and referral to treatment, including an SBI report at monthly trauma conferences, and incorporating SBI into the trauma order set. Outcomes measures were number of patients screened, patients screening positive, and the number of patients receiving SBI. At baseline, 170 of 362 patients (47%) were screened, 68/170 (40%) had positive screens, and 30/68 (44% of those with positive screens) received SBI services. Quarter 2 saw increases in patients screened—275/437 (63%), patients screening positive (106/275; 39%) and those receiving SBI (60/106; 57%). Increases culminated in Quarter 4 with screening 401/466 (86%; P < 0.001) patients, 208/401 (52%; P < 0.001) patients screening positive, and 114 patients (55%; P = 0.296) receiving services. Use of similar quality improvement measures nationwide could improve rates of provision of this important service.